2007
DOI: 10.1109/tasl.2007.899281
|View full text |Cite
|
Sign up to set email alerts
|

Batch and Online Underdetermined Source Separation Using Laplacian Mixture Models

Abstract: Abstract-In this paper, we explore the problem of sound source separation and identification from a two-sensor instantaneous mixture. The estimation of the mixing and the sources is performed using Laplacian Mixture Models (LMM). The proposed algorithm fits the model using batch processing of the observed data and performs separation using either a hard or a soft decision scheme. An extension of the algorithm to online source separation, where the samples are arriving in a realtime fashion, is also presented. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
1
35
0
3
Order By: Relevance
“…In fact, it has been reported that the Laplacian distribution is able to model speech both in the time domain and in the STFT domain [14]. Moreover, due to the peaky nature of the magnitude ratio distribution, Laplacian mixture models have also been employed in underdetermined blind source separation problems [15]. However, while the Laplacian distribution might be suitable to model STFT coefficients under some circumstances [16], the proposed Cauchy-based model for STFT coefficients has been shown to provide better accuracy in our R-D modeling task.…”
Section: A Suitability Of the Modelmentioning
confidence: 99%
“…In fact, it has been reported that the Laplacian distribution is able to model speech both in the time domain and in the STFT domain [14]. Moreover, due to the peaky nature of the magnitude ratio distribution, Laplacian mixture models have also been employed in underdetermined blind source separation problems [15]. However, while the Laplacian distribution might be suitable to model STFT coefficients under some circumstances [16], the proposed Cauchy-based model for STFT coefficients has been shown to provide better accuracy in our R-D modeling task.…”
Section: A Suitability Of the Modelmentioning
confidence: 99%
“…In particular, Laplacian mixture models (LMMs) have been proposed and applied for the purposes of robust clustering and overcomplete source separation [6,14]. Among robust clustering methods [11,10], those based on LMMs provide simple learning algorithms similar to the learning of Gaussian mixture models (GMMs).…”
Section: Introductionmentioning
confidence: 99%
“…In [3], the DOA (based on AVS) and the mixing vector cues (as in [4]) were combined to achieve separation in reverberant environments, where these cues are modelled by (complex) Gaussian distributions. In anechoic situations, however, a Laplacian distribution has been shown to perform well for modelling the mixing vectors [5].…”
Section: Introductionmentioning
confidence: 99%